Online Learning Means: Video Conference Platforms - Kyselova, Olesia (My University, 2022)
The article highlights popular video conferencing platforms as a means of supporting online learning. The positive aspects of using the most popular video conference programs among educators are considered: Zoom, Google Meet, Microsoft Teams. In the conditions of distance learning, the considered video conferencing platforms allow you to organize and support virtual communication and cooperation between participants of the educational process in real time from anywhere in Ukraine or the world, provided there is access to the Internet.
Kyselova O. Online Learning Means : Video Conference Platforms / O. Kyselova // Нотатки сучасної науки: електронний мультидисциплінарний науковий часопис. – Харків : СГ НТМ «Новий курс», 2022. – № 2. – С. 35–37.
Keywords: відеоконференція, дистанційне навчання, віртуальна комунікація, платформи відео конференцій, Zoom, Google Meet, Microsoft Teams; video conference, distance learning, virtual communication, video conference platforms, Zoom, Google Meet, Microsoft Teams